Circular economy practices on wood panels: A bibliographic analysis - Araújo, Cristiane Karyn de Carvalho; Salvador, Rodrigo; Piekarski, Cassiano Moro; Sokulski, Carla Cristiane; de Francisco, Antonio Carlos; Camargo, Sâmique Kyene de Carvalho Araújo [UNESP] (MDPI, 2019)
The scarcity of natural resources and the generation of waste without adequate disposal are a worldwide concern related to the linear production model.These characteristics are present in the wood panel production. Faced with this problem, the present study aimed to identify in the literature, circular economy (CE) practices in the waste management of wood panel production processes and the possibilities for implementing new practices that incorporate circularity concepts. A systematic search was conducted to select the most relevant work on the theme. A search was done using the ScienceDirect,Web of Science, and Scopus databases by combining the following keywords: Circular Economy (and its possible variations), Wood-based Panel, and WoodWaste. The results evidenced circular economy practices on waste management already being used by the wood panel industry, besides potential practices to increase circularity. The changes go towards sustainable manufacturing and responsible consumption, which aims to ensure sustainable consumption and production patterns. Opportunities range from the extraction of raw materials to the disposal of wood panel waste at the end-of-life. The circular economy model is still recent and the process of transitioning is in its initial phase, as well as scientific research on the theme, mainly regarding the wood panel industry. Studies addressing the circular economy and wood panels are not yet widespread, pointing to a gap yet to be explored. The bibliographic review allowed identifying the existence of potential applications of circular economy in the wood panel industry; yet, this piece of research points to a broad field of exploration.
Keywords: Circular economy; Waste; Wood panel